Enhancing the esterification reaction rate in biodiesel production using microwave with iron powder catalysis - Hsien-Wen Chao; Chen-Yi Hsu; Hung-Chun Hsu; Shang-Da Tsai; Yu-Xian Liu; Tsun-Hsu Chang (Applied Catalysis O: Open)
In biodiesel esterification, metal oxides of solid catalysts and magnetic nanoparticles are commonly used. Studies highlight that microwave technology can significantly shorten reaction time and reduce heat waste, making it a key area for future material processing advancements. Metal oxides are less effective than metal particles in concentrating electromagnetic fields. Our research investigated the use of metal particles—iron, cobalt, nickel, and silver—in esterification reactions. Among these, only iron powder demonstrated effective catalytic performance, confirming that this study belongs to the category of heterogeneous catalysis. We found that only iron powder exhibited significant catalytic effects. Building on this, we developed a novel hybrid catalyst—microwave-assisted iron powder—for biofuel esterification. This catalyst enhanced the reaction rate by approximately 14 times compared to conventional methods. We compared iron powder with Fe3O4 and Fe2O3, finding that iron powder outperformed both, demonstrating superior performance in microwave-assisted reactions. Iron powder maintained its original properties without oxidation throughout the reaction, ensuring catalyst stability. Furthermore, we successfully recovered and reused the iron powder, with its catalytic performance remaining consistent after multiple uses. This development offers a more effective and sustainable approach to biofuel production, addressing both efficiency and environmental concerns. The successful implementation of this research highlights the importance of technological innovation and interdisciplinary collaboration in advancing the Sustainable Development Goals (SDGs).